2019
DOI: 10.11606/1807-0205/2019.59.51
|View full text |Cite
|
Sign up to set email alerts
|

New genera records of split-eyed owlflies (Neuroptera: Myrmeleontidae: Ascalaphinae) from Colombia

Abstract: The genera Ameropterus Esben-Petersen, 1922 and Fillus Navás, 1919 are recorded from Colombia for the first time. New distributional records for two Cordulecerus Rambur, 1842 species are also presented. Ameropterus dissimilis (McLachlan, 1871) and Ameropterus scutellaris (Gerstaecker, 1894) are redescribed and illustrated, and Ameropterus mexicanus (Van der Weele, 1909) is here proposed as a junior synonym of the latter. The taxonomic status of Nephelasca crocea Navás, 1914 is discussed. Keys to the Colombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Comments. According to Ardila-Camacho et al (2019), six species occur in Brazil, but until now only C. subiratus Walker, 1853 was known from southern region of Brazil, from Rio Grande do Sul state (Machado and Martins 2021). Herein, we report the first record of C. alopecinus from Fênix, Paraná.…”
Section: Newly Recorded Species In Paranámentioning
confidence: 99%
“…Comments. According to Ardila-Camacho et al (2019), six species occur in Brazil, but until now only C. subiratus Walker, 1853 was known from southern region of Brazil, from Rio Grande do Sul state (Machado and Martins 2021). Herein, we report the first record of C. alopecinus from Fênix, Paraná.…”
Section: Newly Recorded Species In Paranámentioning
confidence: 99%
“…5). Remarks: there are no published faunistic data for the species since the description, only the name can be found in checklists and fauna catalogues (navás 1912c, Penny 1977, heckman 2017, ardila-Camacho et al 2019. It is known in Peru and bolivia (van der Weele 1909).…”
Section: Palpares Torridus Navás 1912mentioning
confidence: 99%
“…Remarks: First, van der Weele (1909) and later, Penny (1977) as well as ardila- Camacho et al (2019) reported specimens from Suriname, Guyana, Brasil and the Dominican republic. navás (1924) cited the occurrence of the species from French Guiana.…”
Section: Cordulecerus Elegans Van Der Weele 1909mentioning
confidence: 99%
See 2 more Smart Citations